Single-shrine temple with a Latina-Nagara Shikhara - Temples of India Project Team (Jio Institute, 2024)
This is a single-shrine temple with a latina-nagara shikhara (mono-spire superstructure) next to the pratoli (entrance gateway), in the row of temples that are along the western boundary of the Mahanaleshwar temple complex. The central band of the shikhara (superstructure) is broader than the rest. The corner bands have karna amalakas (aedicules made of gavaksha or dormer window designs and separated by slender fruit-like ribbed discs). The temple is a simple construction, not austere in appearance and has lost the topmost portion of its shikhara. Latina shikhara in which the central band of the shikhara (superstructure) is broader than the rest. The corner bands have karna amalakas (aedicules made of gavaksha or dormer window designs and separated by slender fruit-like ribbed discs).